SCOTfluors: Small, Conjugatable, Orthogonal, and Tunable Fluorophores for In Vivo Imaging of Cell Metabolism. Issue 21 (12th April 2019) - Benson, Sam; Fernandez, Antonio; Barth, Nicole D.; de Moliner, Fabio; Horrocks, Mathew H.; Herrington, C. Simon; Abad, Jose Luis; Delgado, Antonio; Kelly, Lisa; Chang, Ziyuan; Feng, Yi; Nishiura, Miyako; et al.
Abstract: The transport and trafficking of metabolites are critical for the correct functioning of live cells. However, in situ metabolic imaging studies are hampered by the lack of fluorescent chemical structures that allow direct monitoring of small metabolites under physiological conditions with high spatial and temporal resolution. Herein, we describe SCOTfluors as novel small‐sized multi‐colored fluorophores for real‐time tracking of essential metabolites in live cells and in vivo and for the acquisition of metabolic profiles from human cancer cells of variable origin. Abstract : Small fluorophores : A family of small multi‐color benzodiazole fluorophores for non‐invasive imaging of essential metabolites in live cells and in vivo is described.